Posted by **judy williams** on Saturday, July 2, 2011 at 11:54pm.

. Prove that -x - y = -y – x; for all integers x and y.

## Answer this Question

## Related Questions

- discrete math - Let A= {for all m that's an element of the integers | m=3k+7 for...
- math - Let f:ℤ+ → ℤ+ be the function defined by: for each x &#...
- math help please - Let f:ℤ+ → ℤ+ be the function defined by: ...
- discrete math - Let f:ℤ+ → ℤ+ be the function defined by: for...
- math - prove -x-y=-y-x, for all integers
- Math, Please Help - 1) Given the arithmetic sequence an = 4 - 3(n - 1), what is ...
- Math - 1) Given the arithmetic sequence an = 4 - 3(n - 1), what is the domain ...
- discrete math - use a direct proof to show that the product of two odd numbers ...
- math - prove -x - y = - y - x, for all integers x and y and does part (a) imply ...
- discrete math - 1)prove that if x is rational and x not equal to 0, then 1/x is ...